IMPLEMENTASI SURAT PEMBERITAHUAN PERKEMBANGAN HASIL PENYIDIKAN TERKAIT MEKANISME PENYIDIKAN TINDAK PIDANA DI INDONESIA (STUDI KASUS DI KEPOLISIAN RESOR KOTA PEKANBARU) - Andreas Leonardo; Erdiansyah Erdiansyah; Sukamarriko Andrikasmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
A Notification In ensuring accountability and transparency of investigations orinvestigations, investigators are required to provide SP2HP to the reporting party whetherrequested or not periodically at least once a month. Today there are often cases that SP2HP,which is an obligation of investigators, is not realized or not implemented properly inaccordance with the provisions stipulated in the Police Regulation of the Republic ofIndonesia Number 16 of 2010 which states that SP2HP is public information and is a right forthe reporter. The purpose of the research is to find out the implementation of the InvestigationResult Progress Notification Letter related to the criminal investigation mechanism inIndonesia, as well as to find out the obstacles faced by the police in implementing theInvestigation Result Progress Notification Letter related to the investigation mechanism incriminal acts at the Pekanbaru City Resort Police (Polresta).This type of research is sociological legal research. This research is located at thePekanbaru City Resort Police (Polresta). The data sources used are primary data andsecondary data, data collection techniques in this study are observation, questionnaires,interviews, and literature review, and can be concluded with deductive thinking methods.From the results of the study, it can be concluded that, First, the regulation of thesubmission of SP2HP to the reporter is regulated in the Regulation of the Chief of Police ofthe Republic of Indonesia (Perkap) Number 14 of 2012 concerning Investigation Managementfor the submission of SP2HP, the submission of SP2HP to the reporter at the Pekanbaru CityPolice has not run optimally because there are several obstacles. Second, the reporter doesnot provide a clear address to the investigator of the Criminal Investigation Unit of thePekanbaru City Police, the reporter is not in his place of existence, there are reporters whoonly make reports but have no concern for the continuation of the case, the mobile phonenumber or telephone provided by the reporter is not active or even does not have acommunication device, the public is less aware